PENGUKURAN BEBAN KERJA OPERATOR STACKER RECLAIMER PADA BAGIAN COAL HANDLING DI PLTU CILACAP - Hartomo Hartomo; Sigit Suwarto; Ahmad Padhil (Journal of Industrial Engineering Management, 2019)
I Efforts to determine the level of workload provided to employees is by measuring and evaluating the extent of the workload felt by employees. The higher the workload borne by employees, the higher the pressure, responsibility and targets that must be met by employees. Therefore, this study aims to measure the level of workload on the reclamer stacker Operator in the coal handling section of the Cilacap power plant for 3 work shifts, night, morning and evening shifts. In the process of measuring workload using a set of research questionnaires, 4 variables from the Defense Research Agency Workload Scale (DRAWS) method become the approach or basis for this research. The 4 variables are Input Demand, Central Demand, Output Demand and Time Pressure. Each of these variables represents the work performed by the reclamer stacker Operator. The results showed that for the three work shifts included in the category of overload with the acquisition of an average value of 73% or greater than 60% ( 60%). The level of complexity of work and work activities under pressure can cause workloads to be high which can ultimately lead to work accidents. In addition, from the results of the workload assessment using the DRAWS method, the highest value is found in the Central Demand (CD) variable, which is 80.5%. This means that the Operator feels the work activity on the variable CD is greater when compared to the work activity on other variables